Design and Analysis of a Novel Two Phase Doubly Salient Permanent Magnet Machine - Zhou Zhiqing; Chi Yongbin (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
A novel two-phase doubly salient permanent magnet machine (FMDSPM) with new winding configuration is proposed in this paper. This machine is identical to the existing doubly salient permanent magnet machine (DSPM) with respect to the mechanical structure, whereas the winding configuration is totally different from that in the latter. The structure and operation principle of FMDSPM is analyzed, and power and sizing equations are derived analytically, which provides the designer with initial calculation to determine the motor frame. Allowing for the new winding configuration utilized, the magnetic features of FMDSPM are investigated by using the FEA. The results show that this new machine is suitable to the application of DC square wave, and the output torque produced is smoother due to no cumbersomely commutating torque ripples compared with the existing DSPM. Further, the prototype is fabricated to validate the above analysis. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3912Keywords: